Is Nietzsche a Life-Affirmer?. (19th July 2016) - May, Simon
Abstract: The question of how to affirm one's life in view of suffering and loss is central to Nietzsche's philosophy. He shows, I claim, that one can affirm – take joy or find beauty in – one's life as a whole, conceived as necessary in all its elements, while also despising parts of it. Yet he mostly pictures such life-affirmation as achievable only via an atheistic theodicy that relies on a key ambition of the very system of morality that he famously attacks: namely to explain or justify suffering in terms of a higher end to which it is essential. I argue that affirmation of one's life is more powerful without the crutch of any theodicy, and point to Job as a paragon of one who can affirm his life without seeking an answer to the question of the meaning or value of suffering – indeed who can dispense altogether with that question.